Physician Assisted Death for Psychiatric Suffering: Experiences in the Netherlands - van Veen, SMP; Widdershoven, GAM; Beekman, ATF; Evans, N. (Frontiers in Psychiatry, 2022)
Physician assisted death (PAD) for patients with a psychiatric disorder is a controversial topic of increasing relevance, since a growing number of countries are allowing it. General requirements for PAD include that patients are competent to choose death and that their suffering is unbearable and irremediable. In the Netherlands PAD has been eligible for patients with psychiatric disorders since the 1990s, making it one of the few countries that can offer insights on the practice from real life experience. Much of the literature describing these experiences is only available in Dutch. This article aims to make this knowledge more widely available and provide a comprehensive overview of the experience with PAD for psychiatric suffering in the Netherlands. First, the history of PAD for patients suffering from a psychiatric disorder is described. Second, an overview of relevant rules and regulations governing the practice is given. Third, an overview is provided of the scarce epidemiological data. Finally, we will discuss two major clinical challenges; establishing irremediability and competence.